Find `lim_(x-> -oo) x^2e^(6x)` :

For `x<0` this is equivalent to `lim_(x-> -oo) (x^2)/(e^(6x))` or `(lim_(x-> -oo)x^2)/(lim_(x-> -oo)e^(6x))=(-oo)/(oo)` .

This is an indeterminate form. Since both `x^2` and `e^(6x)` are differentiable, by L'Hopital's Rule we have:

`lim_(x->-oo)(x^2)/(e^(6x))=lim_(x->-oo)(2x)/(6e^(6x))` . This limit also yields the indeterminate form `(-oo)/(oo)` ; both numerator and denominator are differentiable so we can apply L'Hopital's Rule again to get:

`lim_(x->-oo)(2x)/(6e^(6x))=lim_(x->-oo)(2)/(36e^(6x))=0` .

------------------------------------

**Therefore**, `lim_(x->-oo)(x^2)/(e^(6x))=0`

------------------------------------

* Note that exponentials grow far faster than any polynomials, so the denominator grows far faster than the numerator supporting the answer. Also consider the graph:

## We’ll help your grades soar

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now